THE IMPACT OF CHAOTIC FLUX REFLECTION FIELD ON HYDROGEN EVOLUTION REACTION OF WATER ELECTROLYSIS - Nugroho, Willy Satrio; Esiliy , Rehab Ragay; Purnami, Purnami; Sofi'i, Yepy Komaril (International Journal of Mechanical Engineering Technologies and Applications, 2024)
Water electrolysis promises the capability to produce green hydrogen in the future. The efficiency and hydrogen evolution reaction rate (HER) of water electrolysis can be improved through magnetic field assisted electrolysis. External magnetic field exposure improves hydrogen production without requiring complex catalyst synthesis technique. The purpose of this study is to introduce chaos into a magnetic field assisted electrolysis system which disturbs the water molecules stability. The chaos effect was triggered by irregular flux reflection technique. The flux reflection was generated using diamagnetic tourmaline stones which sticked all over the electrolyzer wall. Consequently, the rotational speed of DMF does not reduce the effectiveness of chaotic flux. As a result, the hydrogen bond of the water molecules is destabilized irregularly. In conjuction with that, the bonds are unable to be reformed which make the water molecules continuously in movement. The critical effect of chaotic flux is the shear force that experienced by water molecules. The paramagnetic OH- ion movement is also slowed down so that H+ ion and electrons interaction were occurred in less restrictive manner. Hence, the chaotic magnetic field able to improve HER.  The chaotic flux reflection improves hydrogen production in magnetic field assisted water electrolysis through water properties and ion transfer mechanism modification.